Answer:
(a)
![x\³ - 6x - 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/nl17lv748z3h50jykp4o57iz07vv529xeb.png)
(b) Proved
Explanation:
Given
--- the root
Solving (a): The polynomial
A cubic function is represented as:
![f = (a + b)^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/uadkwbxwvyps0au4zna6tzk0zmwic144pu.png)
Expand
![f = a^3 + 3a^2b + 3ab^2 + b^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/pc4si6r30ssamr98hsxnnq2ga4fbgegvak.png)
Rewrite as:
![f = a^3 + 3ab(a + b) + b^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/fivfthxbpkpzt6x34oertqtje6u5s2cvme.png)
The root is represented as:
![r=a+b](https://img.qammunity.org/2022/formulas/mathematics/high-school/pd97e4cbtzol2qna3yfk6f3sd9ee2k9ld6.png)
By comparison:
![a = $\sqrt[3]{2}](https://img.qammunity.org/2022/formulas/mathematics/high-school/mzr3gcz1w200swmjl2cli5cq5gjqmbwhbm.png)
![b = \sqrt[3]{4}$](https://img.qammunity.org/2022/formulas/mathematics/high-school/lh16d0iezum4q6n3166ocmuzy0zy4h5ryt.png)
So, we have:
![f = ($\sqrt[3]{2})^3 + 3*$\sqrt[3]{2}*\sqrt[3]{4}$*($\sqrt[3]{2} + \sqrt[3]{4}$) + (\sqrt[3]{4}$)^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/csb2rziixlq2ih3hrn3wjabsc2dxiw0u62.png)
Expand
![f = 2 + 3*$\sqrt[3]{2*4}*($\sqrt[3]{2} + \sqrt[3]{4}$) + 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/fmuf51g7qwlz19fsfmaxnpk7x2gghkg9h0.png)
![f = 2 + 3*$\sqrt[3]{8}*($\sqrt[3]{2} + \sqrt[3]{4}$) + 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/6t2wquhyy7rbklkt7zw6c8mjkp1bjggb4m.png)
![f = 2 + 3*2*($\sqrt[3]{2} + \sqrt[3]{4}$) + 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/gf3rgy9lnvx6ulfsy3833ozwml3bk46pjo.png)
![f = 2 + 6($\sqrt[3]{2} + \sqrt[3]{4}$) + 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/m5t8nlidk8szc9p5fti9h3o0368xwachhd.png)
Evaluate like terms
![f = 6 + 6($\sqrt[3]{2} + \sqrt[3]{4}$)](https://img.qammunity.org/2022/formulas/mathematics/high-school/hgxgliw4650fyu9pxic7wetwx612wff111.png)
Recall that:
![r = $\sqrt[3]{2} + \sqrt[3]{4}$](https://img.qammunity.org/2022/formulas/mathematics/high-school/ywbxziya7jn32w43ss8rta7hl7zxghpou9.png)
So, we have:
![f = 6 + 6r](https://img.qammunity.org/2022/formulas/mathematics/high-school/ruu652zu2seg9ydo1rh46d9fbx2gjrpdot.png)
Equate to 0
![f - 6 - 6r = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/w084vf9r9gk03gohomt63azhj196yaevk6.png)
Rewrite as:
![f - 6r - 6 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/pg2frvkwul8zzo702wnq68qk67oth3scf0.png)
Express as a cubic function
![x^3 - 6x - 6 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/617droktzpzrw5d4zdljldeq5lwq14ap6p.png)
Hence, the cubic polynomial is:
![f(x) = x^3 - 6x - 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/zbxuyb8x4e71o6863myrs7554ewaf1ufqj.png)
Solving (b): Prove that r is irrational
The constant term of
is -6
The divisors of -6 are: -6,-3,-2,-1,1,2,3,6
Calculate f(x) for each of the above values to calculate the remainder when f(x) is divided by any of the above values
![f(-6) = (-6)^3 - 6*-6 - 6 = -186](https://img.qammunity.org/2022/formulas/mathematics/high-school/z02nsh49eq011nhpryzxtd4hd4innx5ml2.png)
![f(-3) = (-3)^3 - 6*-3 - 6 = -15](https://img.qammunity.org/2022/formulas/mathematics/high-school/38lmxch0pzqteofndoi5gficowlj6worig.png)
![f(-2) = (-2)^3 - 6*-2 - 6 = -2](https://img.qammunity.org/2022/formulas/mathematics/high-school/vop2tmay5509hze60sknmgztxc02yfz6fp.png)
![f(-1) = (-1)^3 - 6*-1 - 6 = -1](https://img.qammunity.org/2022/formulas/mathematics/high-school/db8bksmm2g0vtaraq6yor9w1kxvhrzdz6s.png)
![f(1) = (1)^3 - 6*1 - 6 = -11](https://img.qammunity.org/2022/formulas/mathematics/high-school/px4vs4jkqvuy8rnpubdery1miypgc2mqkz.png)
![f(2) = (2)^3 - 6*2 - 6 = -10](https://img.qammunity.org/2022/formulas/mathematics/high-school/ju13axoyfv6nbkxp01mbdbra83gop482ov.png)
![f(3) = (3)^3 - 6*3 - 6 = 3](https://img.qammunity.org/2022/formulas/mathematics/high-school/our2imzqql2tx614m27b4k949zmd0rbf7i.png)
![f(6) = (6)^3 - 6*6 - 6 = 174](https://img.qammunity.org/2022/formulas/mathematics/high-school/7lcwk2dlgzw265tvx5sbespaxtlocdrwod.png)
For r to be rational;
The divisors of -6 must divide f(x) without remainder
i.e. Any of the above values must equal 0
Since none equals 0, then r is irrational